2017
DOI: 10.1080/09658211.2017.1322108
|View full text |Cite
|
Sign up to set email alerts
|

Reduced specificity and enhanced subjective experience of future thinking in ageing: the influence of avoidance and emotion-regulation strategies

Abstract: Future thinking in older adults is characterised by a lack of specificity of imagined events and by an equal or even higher subjective experience, compared to younger adults. We considered whether this lack of specificity stemmed partly from the avoidance of a somewhat disturbing future and then examined the extent to which certain types of emotion-regulation strategies, namely positive reappraisal and positive refocusing, contributed to the subjective experience of future thinking. Middle-aged and older adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 87 publications
0
12
1
Order By: Relevance
“…The limitations of the elderly appear in the memory of information that requires attentional and cognitive resources ( Craik and McDowd, 1987 ; Danckert and Craik, 2013 ), such as specific facts or concrete details. In addition, future thinking in older adults is characterized by a lack of specificity of imagined events and by an equal or even higher subjective experience in comparison with younger adults ( Jumentier et al, 2017 ). However, it has been observed that age differences in memory are reduced or even eliminated when participants process emotional or affective information ( May et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The limitations of the elderly appear in the memory of information that requires attentional and cognitive resources ( Craik and McDowd, 1987 ; Danckert and Craik, 2013 ), such as specific facts or concrete details. In addition, future thinking in older adults is characterized by a lack of specificity of imagined events and by an equal or even higher subjective experience in comparison with younger adults ( Jumentier et al, 2017 ). However, it has been observed that age differences in memory are reduced or even eliminated when participants process emotional or affective information ( May et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…Commission errors, when the participants contribute their own or others’ events that are not present in the coding phase, may be connected to prior knowledge ( Migueles and García-Bajos, 2012 ), life scripts ( Rubin and Berntsen, 2003 ), or forms of semantic memory that can be used to guide one’s anticipated future ( Grysman et al, 2015 ). Source errors—in which an error is made regarding the subject or action of an event—can be an index of the lack of specificity of processing the origin of the information ( Danckert and Craik, 2013 ; Jumentier et al, 2017 ) and should depend on the recollection of specific details about the earlier generated events ( Gallo et al, 2011 ). And more relevant to the effect of positivity in the memory of future events would be changes in emotional valence, where negative events are remembered as positive.…”
Section: Introductionmentioning
confidence: 99%
“…The jump between these two future time periods leaves unanswered the question of how far into the future this period of the present future extends, how far into the future the anticipation of older adults remains comparable to that of younger adults. Jumentier et al (2018), using a word-cuing methodology to elicit future thoughts, found older adults to be less specific than younger adults in their future representations, both when cued to think about events in the next year and the next 5–10 years. This study did not include a future time frame shorter than 1 year.…”
Section: Discussionmentioning
confidence: 99%
“…The use of more experimental methodologies such as the Future-Thinking Task (MacLeod et al, 1993) or word-cuing paradigms (e.g., Jumentier et al, 2018; Madore & Schacter, 2014) can provide a useful supplement to existing, questionnaire-based methods for examining future-thinking in older adults. Although such measures do rely on people providing their own subjective responses, they (a) allow people to report on their own idiographic thoughts, (b) enable an examination of the content of people’s thoughts about the future, and (c) produce objective performance indicators such as latency to first response or number of response within a given time limit.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, desirable future events are more vividly and easily imagined, richer in episodic details, and set in a clearer spatio-temporal frame than undesirable scenarios (D'Argembeau & Van der Linden, 2004;de Vito et al, 2015a). Similarly, negative cues and strategies to avoid scaring events can decrease the specificity of future thoughts (Jumentier, Barsics, & Van der Linden, 2017). However, death is somewhat special in that respect, being already certain.…”
Section: Introductionmentioning
confidence: 99%